Retrospective Study on Fatal Melioidosis in Captive Zoo Animals in Thailand. Issue 5 (13th January 2015) - Kasantikul, T.; Sommanustweechai, A.; Polsrila, K.; Kongkham, W.; Chaisongkram, C.; Sanannu, S.; Kongmakee, P.; Narongwanichgarn, W.; Bush, M.; Sermswan, R. W.; Banlunara, W.
Summary: Melioidosis is caused by Burkholderia pseudomallei and is an important zoonotic infectious disease causing high mortality from fulminant septicaemia in humans and a wide variety of animal species. The incidence of fatal melioidosis in zoo animals has been significant in many Thai zoos. A total number of 32 cases were evaluated throughout the Thai zoo animal populations. The highest prevalence of disease has been reported from the north‐eastern region followed by the zoos in the southern part of the country, approximately 47% and 38%, respectively, while the other zoos reported sporadic infections. Herbivores and non‐human primates were the most commonly affected animals with incidences of 59% and 28%, respectively. This appears to be a seasonal correlation with the highest incidence of melioidosis in zoo animals reported in the rainy season (44%) or subdivided monthly in June (19%) followed by September and November (16% and 12%, respectively). The route of infection and the incubation period still remain unclear. This retrospective study examined the clinical presentation in various zoo species, pathological findings and epidemiological data as well as conducting an in depth literature review.